Fighting for the king and the gods: a survey of warfare in the ancient Near East - Trimm, Charlie (Resources for biblical study, 2017)
Old and new military history -- Historicity -- Structure of the book -- Cultural and geographical groupings -- Casus Belli -- Defense -- Protection against chaos -- Acquisition -- Avoiding war -- Preparation for war -- Communication with enemy -- Intelligence -- Mustering troops -- March to war -- The king's role before battle -- Preparing defenses -- Battles -- Open field -- Communication in battle -- Chariots -- Horses (and other animals) -- Sieges -- Naval combat -- Single combat -- Deception in warfare -- Kings and princes in battle -- Results of battles -- Flight -- Plundering and prisoners -- Humiliation of enemies -- Urbicide -- Extermination of enemies -- Political and religious results of conquest -- Other responses to victory -- Responses to defeat -- Conflicted memories -- Officers and soldiers -- Command structure -- Size of armies -- Military scribes -- Training and life at home -- Life on campaign -- Problematic soldiers -- Weapons and armor -- Hand-to-hand weapons -- Distance weapons -- Defensive equipment -- Divine warriors -- Divine combat -- Calls for divine help -- Messages from the divine warriors -- Divine abandonment -- Divine weapons and incorporation into the myths -- Presence in battle